Exon junction complex subunits are required to splice Drosophila MAP kinase, a large heterochromatic gene - Roignant, Jean-Yves (2010)
The exon junction complex (EJC) is assembled on spliced mRNAs upstream of exon-exon junctions, and can regulate their subsequent translation, localization, or degradation. We isolated mutations in Drosophila mago nashi (mago), which encodes a core EJC subunit, based on their unexpectedly specific effects on photoreceptor differentiation. Loss of Mago prevents Epidermal growth factor receptor signaling, due to a large reduction in MAPK mRNA levels. MAPK expression also requires the EJC subunits Y14 and eIF4AIII, and EJC-associated splicing factors. Mago depletion does not affect the transcription or stability of MAPK mRNA, but alters its splicing pattern. MAPK expression from an exogenous promoter requires Mago only when the template includes introns. MAPK is the primary functional target of mago in eye development; in cultured cells, Mago knockdown disproportionately affects other large genes located in heterochromatin. These data support a nuclear role for EJC components in splicing a specific subset of introns.